2010
DOI: 10.2114/jpa2.29.71
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movement Performance and Prefrontal Hemodynamics during Saccadic Eye Movements in the Elderly

Abstract: No previous study has investigated age-related changes in prefrontal hemodynamics during saccade tasks in a large number of elderly adults. The purpose of this study was to evaluate prefrontal activity related to the performance of anti-saccade in the elderly using near-infrared spectroscopy (NIRS). Ninety-six elderly adults and 22 young adults performed pro-and anti-saccade tasks. Measures included reaction times of both saccades, error rate during anti-saccade, and concentration of oxyhemoglobin (Doxy-Hb) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 36 publications
5
11
0
Order By: Relevance
“…In all measurements for both groups, Doxy-Hb was significantly increased by performing anti-saccade, consistent with previous findings (Fujiwara et al 2010). It has been reported that Doxy-Hb in the prefrontal cortex was decreased during anti-saccade in elite basketball players, who could presumably perform the saccade automatically through their sporting experience (Fujiwara et al 2009a).…”
Section: Values Indicate Mean (Sd)supporting
confidence: 91%
See 2 more Smart Citations
“…In all measurements for both groups, Doxy-Hb was significantly increased by performing anti-saccade, consistent with previous findings (Fujiwara et al 2010). It has been reported that Doxy-Hb in the prefrontal cortex was decreased during anti-saccade in elite basketball players, who could presumably perform the saccade automatically through their sporting experience (Fujiwara et al 2009a).…”
Section: Values Indicate Mean (Sd)supporting
confidence: 91%
“…Mean reaction time (312 ms) and error rate (44%) at the neck resting position before training were similar to the same measurement values for many elderly subjects (reaction time 337 ms, error rate, 48%) and were significantly longer and higher, respectively, than those for young subjects in our previous studies (reaction time 263 ms, t 41 = 3.7; error rate 14%, t 39 = 5.9; p \ 0.001) (Fujiwara et al 2009a(Fujiwara et al , 2010. In both training groups, these measurement values were markedly decreased through training, with patterns of change similar to previous data from young subjects (Deng et al 2009;Dyckman and McDowell 2005).…”
Section: Values Indicate Mean (Sd)supporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, several studies focus on the relationship between human emotions and fNIRS signals [37]- [39], and we use fNIRS signals with eye gaze data in this study. There have been some studies in which both fNIRS and eye gaze data were used [40]- [42]. Specifically, in order to obtain fNIRS signals, we measure changes in deoxygenated and oxygenated hemoglobin levels from the head cortex by using near-infrared light.…”
Section: B Extraction Of Brain Activity-based Features and Cca-basedmentioning
confidence: 99%
“…[15][16][17] Blindsight-like phosphene perceptions and saccadic eye movements are, however, completely different from each other. In other words, although pseudo-blindsight induced by ELF stimulations is perceived as a conscious perception, the responses of the stimulated eyeball corresponding to the perception (e.g., some eye motions to the appeared phosphene) are an "unconscious" related to the human bioreactivity.…”
mentioning
confidence: 94%